TEP or TAPP: who, when, and how? - Iossa, Angelo; Traumueller Tamagnini, Giovanni; De Angelis, Francesco; Micalizzi, Alessandra; Lelli, Giulio; Cavallaro, Giuseppe (Frontiers in Surgery, 2024)
Groin hernia repair is the most common procedure performed by general surgeons. Open mesh technique represents, generally, the main technique for an inguinal repair, but often a different approach is required. Laparoscopy was found to be the answer to minimize the impact of the preperitoneal open techniques described by Nyhus and Stoppa. The introduction in the early 90's of totally extraperitoneal hernia repair (TEP) and transabdominal preperitoneal repair (TAPP) started a new chapter in groin hernia surgery. Soon the minimally invasive techniques versus open mesh, and then one against the other became a hot topic among abdominal wall surgeons, and with time the number of procedures and indications increased and are still increasing. This review aims at providing an overview of the two main laparoscopic techniques for groin hernia repair answering the questions: who should perform them? What is the learning curve required to minimize complications and optimize operative time? When is a minimally invasive approach indicated and which one (both in elective and in emergency setting)? How are they performed? The standard techniques have been described in detail and, also, personal observations from an abdominal wall surgery referral centre were added. The main reviews, from the early 2000's up to date, comparing the techniques have been analysed and results reported, confirming the comparable safety and efficacy of both these techniques.